Cannabidiol Rescues Acute Hepatic Toxicity and Seizure Induced by Cocaine - Luciano Rezende Vilela; Lindisley Ferreira Gomides; Bruna Araújo David; Maísa Mota Antunes; Ariane Barros Diniz; Fabrício de Araújo Moreira; Gustavo Batista Menezes (Mediators of Inflammation)
Cocaine is a commonly abused illicit drug that causes significant morbidity and mortality. The most severe and common complications are seizures, ischemic strokes, myocardial infarction, and acute liver injury. Here, we demonstrated that acute cocaine intoxication promoted seizure along with acute liver damage in mice, with intense inflammatory infiltrate. Considering the protective role of the endocannabinoid system against cell toxicity, we hypothesized that treatment with an anandamide hydrolysis inhibitor, URB597, or with a phytocannabinoid, cannabidiol (CBD), protects against cocaine toxicity. URB597 (1.0 mg/kg) abolished cocaine-induced seizure, yet it did not protect against acute liver injury. Using confocal liver intravital microscopy, we observed that CBD (30 mg/kg) reduced acute liver inflammation and damage induced by cocaine and prevented associated seizure. Additionally, we showed that previous liver damage induced by another hepatotoxic drug (acetaminophen) increased seizure and lethality induced by cocaine intoxication, linking hepatotoxicity to seizure dynamics. These findings suggest that activation of cannabinoid system may have protective actions on both liver and brain induced by cocaine, minimizing inflammatory injury promoted by cocaine, supporting its further clinical application in the treatment of cocaine abuse.